Histone Hyperacetylation in Maize in Response to Treatment with HC-Toxin or Infection by the Filamentous Fungus Cochliobolus carbonum. - Ransom, R. F. (1997)
HC-toxin, the host-selective toxin produced by the filamentous fungus Cochliobolus carbonum, inhibits maize (Zea mays L.) histone deacetylases (HDs) in vitro. Here we show that HDs are also inhibited by HC-toxin in vivo, as demonstrated by the accumulation of hyperacetylated forms of the core (nucleosomal) histones H3.1, H3.2, H3.3, and H4 in both maize embryos and tissue cultures. Hyperacetylation of H4 and all isoforms of H3 in tissue cultures of inbred Pr (genotype hm/hm) occurred at 10 ng/mL (23 nM). The effect was host-selective; acetylation of histones in the near isogenic inbred Pr1 (genotype Hm/Hm) did not occur in tissue cultures or embryos treated with 0.2 [mu]g/mL or 10 [mu]g/mL HC-toxin, respectively. Hyperacetylation of histone H4 in embryos of Pr1 began to occur at 50 [mu]g/mL. HC-toxin, and 200 [mu]g/mL HC-toxin caused equal hyperacetylation in Pr and Pr1 embryos. Hyperacetylated core histones, especially of the isoforms of histone H3, accumulated in leaves of inbred Pr, but not Pr1, after infection by toxin-producing strains of C. carbonum. Accumulation of hyperacetylated histones began at 24 h after inoculation, before the development of visible disease symptoms. Hyperacetylation of H2A or H2B histones were not detected in any of the studies. The results are consistent with HD being a primary site of action of HC-toxin.